Antimicrobial activity of biochemical substances against pathogens of cultivated mushrooms in Serbia - Potočnik, Ivana S; Todorović, Biljana; Đurović-Pejčev, Rada; Stepanović, Miloš; Rekanović, Emil; Milijašević-Marčić, Svetlana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
Disease control with few or no chemicals is a major challenge for mushroom growers in the 21st century. An alarming incidence of resistance to antibiotics in bacteria, and to fungicides among mycopathogenic fungi requires effective alternatives. Previous studies have indicated that various plant oils and their components demonstrate strong antimicrobial effects against pathogens on cultivated mushrooms. The strongest and broadest activity to pathogens obtained from mushroom facilities in Serbia was shown by the oils of oregano, thyme and basil. Five oils inhibited the growth of pathogenic bacteria Pseudomonas tolaasii: wintergreen, oregano, lemongrass, rosemary and eucalyptus. The essential oils of oregano, geranium and thyme were considerably toxic to the pathogenic fungi Mycogone perniciosa, Lecanicillium fungicola and Cladobotryum spp. The strongest activity against Trichoderma aggressivum f. europaeum was shown by the oils of basil and mint. Oils of juniper and pine showed neither inhibitory nor lethal effects on mushroom pathogens. Although the fungitoxic activity of oils is not strong, they could be used as a supplement to commercial productus for disease control, which will minimize the quantity of fungicides used.